2001
DOI: 10.1053/jlts.2001.27856
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for liver transplantation in early-stage hepatocellular carcinoma with cirrhosis: Results of a multicenter study

Abstract: Orthotopic liver transplantation (OLT) offers the only chance to eliminate both tumor and liver disease in patients with hepatocellular carcinoma (HCC) and cirrhosis. However, tumor progression while on the waiting list and recurrence after OLT are frequent. We undertook a large multicenter study to assess survival and related factors of recurrence after OLT. This retrospective study analyses data from 307 consecutive patients with HCC and cirrhosis treated with OLT between 1990 and 1997 in eight centers in Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 15 publications
4
106
1
4
Order By: Relevance
“…With the improvement in surgical techniques and better immunosuppressants to reduce the risk of graft rejection, the hospital mortality rate is less than 5% in major centers and the 5-year survival rate is about 60-75% [269][270][271][272][273]. Tumor recurrence after transplantation is lower than after resection for small HCC, and the 5-year disease-free survival rate is about 60-70%.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…With the improvement in surgical techniques and better immunosuppressants to reduce the risk of graft rejection, the hospital mortality rate is less than 5% in major centers and the 5-year survival rate is about 60-75% [269][270][271][272][273]. Tumor recurrence after transplantation is lower than after resection for small HCC, and the 5-year disease-free survival rate is about 60-70%.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…AFP has been studied in a series of mainly single-center retrospective reviews for its ability to predict posttransplant outcomes; predictive power has been reported at cutoff values ranging from >10 to > 1000 ng/mL. 17,[19][20][21][22][23][24][25][26][27][28][29][30] Despite an abundance of data, AFP has not yet been widely adopted as a selection criterion.…”
Section: Candidate Biomarkersmentioning
confidence: 99%
“…This finding confirms that incidental HCC, despite the fact that the nodules are small, may have features of advanced malignancy and can recur after LT. 8,9 In our cohort, patients with a single tumor nodule with a maximum diameter of 5 cm; or up to 3 nodules, all less than 4.5 cm each with a cumulative diameter up to 8 cm; or more than 3 nodules is predictive of HCC recurrence. 10 Furthermore, a rapid increase in serum AFP before transplant might identify a tumor with highly malignant behavior, and might explain our observation that a rapid pre-LT increase was associated with post-LT recurrence. These data suggests the dynamic evaluation of AFP levels could be included in the pre-LT assessment.…”
Section: Discussionmentioning
confidence: 47%